2014
DOI: 10.1002/2014ja020307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Martian crustal magnetic anomalies on the emission of energetic neutral hydrogen atoms

Abstract: We analyze the data on hydrogen energetic neutral atoms (ENAs) emissions from the dayside of Mars, recorded by a Neutral Particle Detector of the Analyzer of Space Plasmas and Energetic Atoms aboard Mars Express from 14 March to 9 July 2004. We first identify and analyze events of the ENA flux enhancement coinciding with the presence of the crustal magnetic anomalies on the dayside of Mars. We then backtrace the ENA emissions to the lower altitudes (source region) and build up an average map of the flux intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The H‐ENA diagnostics allow remote imaging of the neutral density distribution and plasma flux distribution. At Mars, the H‐ENA imaging has revealed a deflection of solar wind protons at the subsolar point (Futaana, Barabash, Holmström, et al, ), a global asymmetry in the magnetosheath proton flow (Wang et al, , ), and oscillations of the magnetospheric plasma flow (Grigoriev et al, ). We will show in section that the precipitating H‐ENAs can be used to constrain the exospheric density of Mars and its annual variability.…”
Section: Introductionmentioning
confidence: 99%
“…The H‐ENA diagnostics allow remote imaging of the neutral density distribution and plasma flux distribution. At Mars, the H‐ENA imaging has revealed a deflection of solar wind protons at the subsolar point (Futaana, Barabash, Holmström, et al, ), a global asymmetry in the magnetosheath proton flow (Wang et al, , ), and oscillations of the magnetospheric plasma flow (Grigoriev et al, ). We will show in section that the precipitating H‐ENAs can be used to constrain the exospheric density of Mars and its annual variability.…”
Section: Introductionmentioning
confidence: 99%
“…These processes result in angular spreading, energy deposition, and backscattering of a fraction of the precipitating flux of H ENAs (Kallio & Barabash, 2001;Shematovich et al, 2011). These hydrogen ENAs, together with H atoms produced in the solar wind and magnetosheath (Gunell et al, 2006) and the backscattered population (Futaana et al, 2006;Mura et al, 2008;Wang et al, 2013Wang et al, , 2014, were observed in the Martian system by the ASPERA-3 instrument onboard MEX. A fraction of the hydrogen atoms (both incoming and backscattered) interact with the atmosphere in charge-exchange reactions and become protons again.…”
Section: Introductionmentioning
confidence: 99%
“…These models have been used to understand an extensive array of Martian plasma processes and interactions. Plasma boundaries (Bertucci et al, ; Bößwetter et al, ; Najib et al, ), spatial ion distribution (Najib et al, ), ion escape (Brecht et al, ; Brecht & Ledvina, ; Dong, Fang et al, ; Fang et al, ; Kallio, Fedorov et al, ), magnetic topology (Liemohn et al, ), energetic neutral atoms (ENAs; Gunell et al, ; Kallio, Barabash et al, ; Wang et al, , ), solar wind alpha particles (Chanteur et al, ), and X‐ray emission (Gunell et al, ) have all been studied using Martian plasma models. Transient processes including coronal mass ejection (CMEs; Dong, Ma, et al, ; Ma et al, ), changes in dynamic pressure (Ma et al, ), changes in solar extreme ultraviolet (EUV) flux (Modolo et al, , ), seasonal variation (Dong et al, ), and crustal field rotation (Fang et al, ; Ma et al, ) have also been topics of study.…”
Section: Introductionmentioning
confidence: 99%